On the Form and Content of a Forensic Handwriting Expert’s Opinion - M. V. Zhizhina; I. R. Yagut’yan (Теория и практика судебной экспертизы)
The content of a forensic handwriting expert’s opinion has been holding attention of both research scientists and practicing experts for many decades now since it is not only an essential evidence in court often being crucial to deciding on a case but also a document bringing together procedural and scientific methodological elements.   Forensic handwriting examination is much in demand for court, it is also profoundly and comprehensively developed, supported by detailed methodological recommendations on drafting and processing of an expert’s opinion. However, the analysis of experts’ opinions from state forensic institutions as well as from non-state brought to light several shortcomings which do not enhance their evidentiary status. This applies in particular to performing the forensic examination by non-state experts who tend to lack competence. At the same time the number of forensic handwriting examinations assigned by court to the non-state forensic institutions prevails significantly.The most common mistakes made by the handwriting experts when drafting opinions are reviewed in the article, some ways to resolve them are proposed. The need to provide methodological recommendations for forensic handwriting experts incorporating current requirements to the experts’ opinions is acknowledged.